Pelatihan Peningkatan Kemampuan Desain Grafis Siswa SMA Panti Asuhan Bani Adam As - Raissa Amanda Putri; Triase Triase; Muhammad Dedi Irawan; Adnan Buyung Nasution; Aninda Muliani; M. Fakhriza (Jurnal Abdi Mas Adzkia, 2021)
ABSTRACT. This Community service was carried out at the Bani Adam As Orphanage which is located at Jalan Mangaan 3 Pasar 2 Mabar, Medan Deli District. This orphanage cares for and meets the needs of orphans and neglected children, from food to school needs from elementary to high school levels. Currently, Bani Adam As Orphanage High School students does not yet have adequate computer laboratories so that their ability to use computer applications is still very limited. For this reason, in order to increase students' abilities in using computer applications, especially to improve graphic design skills, training was conducted to improve graphic design skills for Bani Adam As Orphanage High School Students. Keywords: graphic, design, computer application